Skrining dan Penyuluhan Kesehatan dalam Mewujudkan Gerakan Masyarakat Hidup Sehat dan Produktif - Umniyatun, Yuyun; Nurmansyah, Mochamad Iqbal; Hidayati, Hidayati; Jacoeb, Teuku Nebrisa Zagladin (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
This article aimed to described community development process that held by collaboration between private hospital and university on sreening and education of health towards implementation of healthy lifestyle of community. These activities have been implemented during November 2018 – January 2019. The event was held on Sammarie Basra Hospital, East Jakarta, Jakarta Province. The event involved 100 people as participant of the health education and screening. The program comprised of some activities such as coordination meeting, development of health promotion media which is in this program, we developed 3 different posters that stick on the Hospital, leaflet that given for the participant and video of psychal activity. Health education has been performed by medical doctor and midwive and health screening by hospital healthcare workers. Participants who got some health screening such as blood pressure, cholesterol, puric acid and glucose test. Most of participants were female (72.7%) with age more than 45 years old (50.0%). The nuber of female participants (30.0%) who have high blood pressure were higher than male participants (16.7%) while the number of male participants who have high DM type 2 and hypercholesterol were higher than female participants, respectively 16.7%/64.3% and 5.0%/36.0%.